100% Renewable energy planning with complementarity and flexibility based on a multi-objective assessment. (1st December 2019) - Luz, Thiago; Moura, Pedro
Highlights: A model for multi-objective power generation expansion planning is proposed. The complementarity between sources and regions and total cost are optimized. Scenarios for the Brazilian 100% renewable energy transition roadmap are presented. The complementarity can reduce the reservoir requirements and hydro dependence. The future energy demand can be to ensure without increasing the reservoir capacity. Abstract: The decarbonization of the power sector has led many academic, governmental and non-governmental institutions to design scenarios with 100% renewable energy and several options to compensate the mismatch between demand and generation have been presented. This paper addresses the benefits to renewable energy integration ensured by the complementarity, and flexibility options, such as demand-side management and batteries. A non-linear multi-objective problem is proposed that maximizes the complementarity and minimizes the total expansion cost. The model also optimizes the battery integration, complementarity between sources and regions, costs, demand-side management, hydropower storage requirements and spatial technology distribution with hourly resolution. The methodology is implemented for the Brazilian case and a scenario able to guarantee three consecutive years of extreme drought in 2050 is presented, without the need of new large reservoirs. Such scenario is ensured with 10% of solar energy, 43% of wind energy, 4.3% of biomass, 41% of hydropower and 1.7% of demand-side management.